Pengaruh Kombinasi Teofilin Dan Ekstrak Bawang Putih (Allium sativum) Terhadap Diameter Lumen Bronkiolus Mencit Asma - Dian Arsanti Palupi; Miyati Miyati; Hasty Martha Wijaya (Universitas Muhammadiyah Surakarta, 2021)
The prevalence of asthma in Indonesia is between 5-7% and is the top 10 causes of morbidity and mortality in severe asthma. Asthma is an inflammation of the respiratory tract which is characterized by spastic constriction of the smooth muscles of the bronchioles, local oedema in the walls of the bronchioles and thick mucus secretions in the lumen of the bronchioles which causes difficulty in breathing. Garlic contains the active compound allicin flavonoids which have long been used as therapeutic ingredients ranging from antibacterial, antiviral, antifungal, antithrombotic, antibiotic, anticancer, antioxidant, immunomodulatory, anti-inflammatory, and hypoglycemic effects. The anti-inflammatory and antioxidant activity of garlic extract can increase the diameter of the bronchial lumen of asthmatic mice. The research method is Post-test Only Control Group Design. using 25 female Balb/C mice aged 2-3 months. Five normal control mice (K1) were not induced by ovalbumin (OVA) and were only treated with CMC Na orally. Meanwhile, 20 other mice were induced by intraperitoneal OVA on days 0 and 7 and then divided into 4 groups, namely negative control (K2) given CMC Na, group K3 given theophylline 0.338 mg/day orally, group K4 given onion extract. 7.8 mg/day orally, group K5 was given a combination of theophylline 0.338 mg/day and garlic extract 7.8 mg/day orally. On days 14, 16 and 18, ovalbumin was administered by inhalation. Administration of the test preparation was carried out on the 18th day to the 32nd day orally, 24 hours after the final exposure, the mice were sacrificed for histopathological testing and observation of the diameter of the bronchiolar lumen with Hematoxylin Eosin staining. The results showed that the combination of theophylline and garlic extract could increase the diameter of the bronchiolus lumen with a p-value = 0.001, so it can be concluded that the combination of theophylline and garlic extract was proven to be statistically significant in increasing the bronchiolar lumen diameter of asthmatic mice.